A study of the influence of the T2DL.2DS-2SS translocation and the 5S(5D) substitution from Aegilops speltoides on breeding-valuable traits of common wheat - R. O. Davoyan; I. V. Bebykina; E. R. Davoyan; A. N. Zinchenko; Y. S. Zubanova; D. M. Boldakov; V. I. Basov; E. D. Badaeva; I. G. Adonina; E. A. Salina (Вавиловский журнал генетики и селекции)
The use of the gene pool of wild relatives for expanding the genetic diversity of common wheat is an important task of breeding programs. However, the practical application of common wheat lines with alien genetic material is constrained by the lack of information on chromosomal rearrangements and the negative impact of the transferred material on agronomically important traits. This research is aimed at studying 14 introgression lines with the T2DL.2DS-2SS translocation and the 5S(5D) substitution from Aegilops speltoides obtained from crossing common wheat varieties (Aurora, Krasnodarskaya 99, Nika Kubani) with the genome-substituted form Avrodes (BBAASS). Hybrid lines with diﬀerent combinations of T2DL.2DS-2SS and T1BL.1RS translocations and 5S(5D) substitution were characterized by resistance to leaf and yellow rusts, productivity components and technological qualities of grain. The assessment of the varieties’ resistance to rust diseases showed that Krasnodarskaya 99, Nika Kubani and the Aurora variety, which is a carrier of the T1BL.1RS translocation, are highly susceptible to diseases, while the presence of the T2DL.2DS-2SS translocation and the 5S(5D) substitution, both together and separately, provides resistance to fungal pathogens. The analysis of the lines using markers designed for known resistance genes of Ae. speltoides did not reveal the presence of the Lr28, Lr35 and Lr51 genes in the lines. The results suggest that the genetic material of Ae. speltoides transferred to chromosomes 2D and 5D contains new resistance genes. To determine the eﬀect of the T2DL.2DS-2SS translocation and the 5S(5D) substitution on the productivity and technological qualities of grain, the lines were assessed by weight of 1000 grains, grain weight and number of ears per 1 m2, by protein and gluten content, gluten quality and general baking evaluation. A positive eﬀect was determined upon the weight of 1000 grains, protein and gluten content. There were no signiﬁcant diﬀerences in other characteristics. The T2DL.2DS-2SS trans-location and the 5S(5D) substitution did not have a negative eﬀect on the productivity and technological quality of grain, and are of interest for breeding practice.